Teaching Style Portrayed in Dead Poets’ Society Film - Taufiq, Ahmad; Islam, Syaiful (International Journal of English Education and Linguistics (IJoEEL), 2021)
Education cannot be separated from the role of a teacher and the teaching style used. The teaching style is a technique in presenting the teaching content. So that the teaching style can attract students' interest. Dead Poets Society is an educational film with the theme of Education. This film tells the story of an English teacher who inspires his students by teaching poetry using his unique teaching style named John Keating. He uses a different teaching style from other teachers in giving lessons till the students are interested to learn poetry. The object of this research is the main character in this film that is Mr. John Keating and the students’ interest in the teaching style used by the main character. The method This research uses qualitative descriptive. The result of this research was found that there were two types of teaching styles used by the main character in Dead Poets Society film. Those are Personalize Teaching Style and Interactional Teaching Style. Meanwhile, the students’ interest in responding to the teaching style used by the main character are only some of the appropriate indicators, those are Concentration while learning, focusing while the teacher explains the material, Enthusiastic to follow the lesson, trying to do the task difficult as any, enjoying in doing the task or exercise given by the teacher at school, having a high enthusiastic to the lesson and the teacher, and the last is answering the question from the teacher.